Description of a new species resembling Paratrichius circularis Ma, 1990 (Coleoptera: Scarabaeidae: Cetoniinae) from China - Mückstein, Petr; Xu, Hao; Qiu, Jian-Yue (Zootaxa, 2020)
Supplementary description and new distributional records are presented for the rare Chinese species Paratrichius circularis Ma, 1990, and a resembling species, Paratrichius tesari Mückstein, Xu & Qiu, new species, is described from Guizhou, China. Habitus, diagnostic characters and ecological notes are illustrated for both species.